The administration of adjuvant chemo(-immuno) therapy in the post ACOSOG-Z0011 era; a population based study. Issue 8 (August 2018) - Poodt, Ingrid G.M.; Rots, Marjolijn L.; Vugts, Guusje; van Dalen, Thijs; Kuijer, Anne; Vriens, Birgit E.P.J.; Nieuwenhuijzen, Grard A.P.; Schipper, Robert-Jan
Abstract: Purpose: The ACOSOG-Z0011-study has resulted in a trend to a more conservative treatment of the axilla for selected sentinel-node-positive patients. However, axillary nodal involvement has always been an important factor for tumor staging and tailoring adjuvant chemotherapy plans. This study evaluates the impact of omitting completion axillary lymph node dissection (cALND) on the administration of adjuvant chemo (-immuno)therapy in Dutch clinical T1-2N0M0 (cT1-2N0M0) sentinel-node-positive breast cancer patients. Methods: Data were obtained from the nationwide NABON breast cancer audit. Descriptive analyses were used to demonstrate trends in axillary surgery and adjuvant chemo (-immuno)therapy. Multivariable logistic regression analyses were used to identify factors associated with the prescription of chemo (-immuno)therapy. Results: In this cohort of 4331 patients, the omission of a cALND increased from 34% to 92%, and the administration of chemo (-immuno)therapy decreased from 68% to 55%, between 2011 and 2015 ( P  < 0.001). Patients treated with cALND had an OR of 2.2 for receiving adjuvant chemo (-immuno)therapy compared with SLNB only patients. Lower age, a hormone receptor (HR) status other than HR-positive, HER2-negative, increasing tumor grade and stage, and a lymph node status ≥ pN2 were independently associated with a higher probability of chemo (-immuno)therapy ( P  < 0.05). Conclusions: This study showed that Dutch cT1-2N0M0 sentinel node-positive breast cancer patients treated with cALND had a higher independent probability for receiving adjuvant chemo (-immuno)therapy compared with SLNB only patients, even when corrected for lymph node status and HR-status. Probably, the decisions to administer adjuvant chemo (-immuno)therapy were not only based on guidelines and tumor characteristics, but also on the preferences from physicians and patients.